Microsporogenesis and ultrastructure of pollen grains of the Andean blackberry Rubus glaucus (Rosaceae) - Rincón-Barón, Edgar Javier; Torres-Rodríguez, Gerardo Andrés; Zarate, Diego A.; Cuarán, Viviana Lucia; Santos-Heredia, Carolina; Passarelli, Lilian M. (Revista de Biología Tropical, 2024)
Introduction: Studies on the microsporogenesis of Rubus glaucus are non-existent and little is known about the ultrastructure of the pollen grains. Objectives: To describe the microsporogenesis process, and ultrastructural aspects of the pollen grains in Rubus glaucus. Methods: Flowers at different developmental stages were embedded in paraffin. Sections were stained with Safranin-Alcian Blue, PAS-Amidoblack and Lacmoid or included in resin and stained with toluidine blue. Ultrathin sections were examined by transmission electron microscopy (TEM). For scanning electron microscopy (SEM) observation, the material was fixed and dehydrated in 2.2 dimethoxypropane, then with Hexamethyldisilazane (HMDS), and the samples were coated with gold. Results: Anthers are differentiated by a cellular mass at the ends distal to the staminal filaments. During development, the anther wall presents several cellular layers and at maturity, they are reduced to the epidermis and the endothecium. Microsporocytes undergo simultaneous meiosis and form tetrahedral tetrads. The tapetum develops secretory activity until pollen grains are released, then the cellular content undergoes autolysis. During sporodermis formation, the exine is first deposited and then the intine in a centripetal form. The pollen grains are tricolporate, isopolar, oblate to peroblate, with radial simetry, circular in outline with blunt apices in polar view, ellipsoidal in equatorial view. The exine is thick, tectated, striate perforate. The sporodermis presents an ectexine formed by a tectum interrupted by perforations and thick columellae. Colpus membrane presents small exine granules and orbicules on the surface. The intine develops known structural patterns. Pollenkitt is inconspicuous. Conclusion: Anthers structure and development follows the known patterns of angiosperms. Simultaneous microsporogenesis and centripetal deposition of the sporodermis, as well as ornamentation patterns, have been previously described for the Rosaceae Family.